Determination of the Important Alfalfa Diseases Occurring in the Alfalfa Growing Areas of the Faculty of Agriculture of Ankara University - Mihrace Çiğdem Onar; Aziz Karakaya (Journal of Agricultural Sciences)
In this study, important alfalfa diseases occurring in the Ankara University Faculty of Agriculture Haymana and Ayaş Research Farms and Dışkapı Campus were determined. Samples were collected during the years 2003 and 2004 and causal agents of the diseases were identified. The fungi found were: Phoma medicaginis var. medicaginis, Leptotrochila medicaginis, Leveillula taurica, Pseudopeziza medicaginis, Peronospora trifoliorum, Stemphylium botryosum, Stagonospora meliloti, Colletotrichum trifolii, Leptosphaerulina briosiana and Rhizoctonia solani. The incidence of Phoma medicaginis var. medicaginis was the highest. Leptosphaerulina briosiana is a new fungus record for Turkey. Alfalfa mosaic virus was also found